Influence of Mining Layout on Efficiency of NRE Drill Rig - Vječislav Bohanek; Paulo Pleše; Sibila Borojević Šoštarić; Ruža Purkić; Ema Vokić (Mining)
The selection of an appropriate mining method, along with the corresponding machinery, is a crucial and highly strategic decision in the field of mining engineering. This decision directly influences the efficiency, safety, and economic viability of a mining operation. An optimal combination of mining techniques and equipment is essential to ensure the effective exploitation of the ore deposit while minimizing costs and maximizing productivity. This paper briefly overviews existing mechanized mining machines for narrow reef mining. The NRE fleet is presented in more detail, together with the results of trial tests conducted using the NRE Drill Rig in narrow reef platinum mines situated in the Great Dyke of Zimbabwe and the Bushveld Igneous Complex in South Africa. The trials were carried out using two distinct mining layouts: the bord and pillar layout and the breast mining layout. The test results clearly demonstrated that the Drill Rig is more effective in breast mining layout compared to the bord and pillar layout in narrow reef mining. The breast mining layout showed superior performance in terms of the number of drilled boreholes and overall efficiency despite the lower availability and utilization of the Drill Rig.